Genetic polymorphism of Populus pruinosa and Populus euphratica in Kazakhstan based on ISSR markers - DINARA AKHATAYEVA; MAKSIM KUTSEV; POLINA VESSELOVA; ZARINA INELOVA; BEKTEMIR OSMONALI; MENGTAY AITZHAN; YELENA ZAPARINA; LAURA SHADMANOVA; EMIL BOROS (Society for Indonesian Biodiversity, 2025)
Abstract. Akhatayeva D, Kutsev M, Vesselova P, Inelova Z, Osmonali B, Aitzhan M, Zaparina Y, Shadmanova L, Boros E. 2025. Genetic polymorphism of Populus pruinosa and Populus euphratica in Kazakhstan based on ISSR markers. Biodiversitas 26: 6120-6129. The genus Populus (Salicaceae) in Kazakhstan is represented by 13 species, although the exact number of species, including varieties and hybrids, has not been clearly established. Among them, Populus pruinosa and Populus euphratica are native species with rapidly declining population sizes and shrinking habitats. Comprehensive studies on their biology and genetic diversity in Kazakhstan have not reported so far. This study aimed to assess genetic diversity, compare patterns of differentiation, evaluate the relationship between genetic variation and ecological conditions in natural populations of both species. Genetic variability was assessed using the ISSR method, and statistical analysis was performed using ANOVA. Samples from six natural populations in southern Kazakhstan (three populations of P. pruinosa and three of P. euphratica) showed distinct interspecific differentiation and variable genetic diversity. P. pruinosa populations had higher allelic diversity (h = 0.114-0.153) and expected heterozygosity (0.107-0.139) than P. euphratica (h = 0.041-0.085). Greater genetic diversity in P. pruinosa indicates stronger adaptive potential to arid environments. A moderate correlation was found between genetic and geographic distances (r = 0.597). The findings highlight P. pruinosa superior ecological adaptability. Both species are recommended for targeted conservation and restoration of arid ecosystems in Kazakhstan.